Managing Agricultural Production by Minimising Environmental Risks: A Study of Farmers Perception of Environmental Risk in Pesticide Use - M.S. Rao; V.K. Dubey (Journal of Agricultural Extension Management, 2025)
With the growing demand for enhancing food grain production to feed more than 90 crores people at one end and increasing yield loss due to pest infestation on the other, the farmers of India till recently, have been relying on chemical fertilizers and pesticides. It is estimated that about thirty percent of the potential of food production is lost due to insect pests, diseases, weeds, rodents and birds. In terms of money, it is estimated that every year crops worth Rs.6000 crore are lost due to pests (Sheth 1994). The demand for pesticides from the agricultural sector during 1989-90 was placed at 70, 000 tonnes. It may go up to 97, 000 tonnes by 2000 A.D. By that time, demand from public health sector may be around 21, 000 tonnes. Thus, the total demand for pesticides by 2000 A.D. may be around 118, 000 tonnes, (Sundaram 1992)